Sanksi Hukuman Mati Terhadap Pembunuhan Non-Muslim (Studi Komparatif Imam AbÅ« á¸¤anÄ«fah dan Imam al-SyÄfiâ€™Ä«) - Iskandar; Ariesman; Afandi, Iman (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2021)
The purpose of this study is to determine the thoughts of Imam AbÅ« á¸¤anÄ«fah and Imam al-SyÄfi'Ä« regarding the death penalty for killing non-Muslims in the perspective of Islamic law and to determine the istinbat method of Imam AbÅ« á¸¤anÄ«fah and Imam al-SyÄfi'Ä« in determining the death penalty. against the killing of non-Muslims. This research is a type of library research, namely research conducted by examining the literature that specifically discusses the death penalty for the perpetrators of the murder. This literature both come from books, books of scholars, and journals. After reviewing the literature, a comparative analysis was carried out by comparing opinions and their arguments. The results of this study are: (1) Imam AbÅ« á¸¤anÄ«fah in determining the death penalty, emphasizes the aspects of equality and equality of a Muslim and non muslim in the eyes of law while Imam al-SyÄfi'Ä« looks at the aspect of belief, if the same is in belief then it is applied death penalty, if different in belief then there is no death penalty. (2) The imposition of the death penalty for killing non-Muslims between Imam AbÅ« á¸¤anÄ«fah and Imam al-SyÄfi'Ä« differs in understanding passages from the al-Qur'an, sunnah and qiyas.